KARAKTERISTIK DEWAN DAN KINERJA BANK: DENGAN UKURAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Muhamad Umar Mai; Sudradjat Sudradjat (Jurnal Riset Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine the moderation of audit committee size on the effect of board characteristics on bank performance on the Indonesia Stock Exchange for the 2016-2020 period. The data analysis method used Partial Least Square-Structural Equation Modeling (PLS-SEM) which was processed with Warp-PLS software. The results of the analysis show that the size of the board of directors, independent board of commissioners, and female board of directors has a positive effect on bank performance, both Return on Assets (ROA) and Return on Equity (ROE). Board of directors meeting has a positive effect on ROE, but has no effect on ROA. Furthermore, the results of the analysis show that the size of the audit committee moderates the effect of the independent board of commissioners on bank performance, as measured by ROA and ROE.